Gender and Identity in Prison - Smoyer, Amy B. (The SAGE Encyclopedia of Criminal Psychology, 2019)
Keywords: dept.swk; gender identity; identity; prisons

Louis Lowy: Lehren aus dem Holocaust - Sozialarbeit unter extremen Bedingungen - Gardella, Lorrie Greenhouse (Lambertus-Verlag, 2019)
Keywords: Biography; Biography; Jewish refugees; Biography; Jews; Biography; Jews, Czech; Biography; Social workers; Boston; Czech Republic; Deggendorf; Germany; Lowy, Louis; Holocaust survivors; Massachusetts; Prague; United States; dept.swk; faculty_collection

Group Work: Creating Space for All Voices - International Association for Social Work with Groups International Symposium Chapel Hill, North Carolina); Gardella, Lorrie Greenhouse; Tully, Greg (Whiting & Birch Ltd., 2019)
Keywords: Congresses; Social group work; dept.swk

Developing a financial literacy program with survivors of intimate partner violence: The voices of survivors - Stylianou, A.M.; Counselman-Carpenter, E.; Redcay, A. (Social Work (United States), 2019)
As the social work field increasingly recognizes economic abuse within intimate partner relationships, the field has developed financial empowerment programs to empower survivors for their financial future. Although research has demonstrated the effectiveness of financial literacy programs, there are barriers to their implementation in the field. Studies have explored, from the perspective of advocates, best practices in incorporating financial literacy into services; however, no studies have explored implementation approaches from the perspective of survivors. This study explores, from the perspective of 34 survivors, approaches for implementing financial literacy programming. Participants described their understanding of financial empowerment as being in charge of finances, having financial power, and not having to endure the struggle. To counter financial disempowerment, participants identified the need for financial confidence, knowledge, and tools. Participants shared their strategies for saving money, though many participants reported barriers to using banks as savings tools. Almost all participants stressed the importance of financial literacy services for survivors, especially around banking, credit, and debt. Finally, participants shared recommendations for job readiness and training programming. Findings have implications for domestic violence and broader social work organizations implementing financial empowerment services. Social workers can support financial empowerment efforts through program development and research efforts. © 2019 National Association of Social Workers.
Keywords: Adult; Crisis and trauma; Female; Financing, Personal; Humans; Intimate Partner Violence; Literacy; Male; Power, Psychological; Program Evaluation; Qualitative methods; Service delivery; Social Work; Social work practice; Survivors; adult; dept.swk; female; financial management; human; literacy; male; partner violence; peer-reviewed; procedures; program evaluation; psychology; social work; survivor

Group Well-Child Care and Health Services Utilization: A Bilingual Qualitative Analysis of Parents' Perspectives. - Oldfield, Benjamin J; Nogelo, Patricia F; Vazquez, Marietta; Ona Ayala, Kimberly; Fenick, Ada M; Rosenthal, Marjorie S (Maternal and child health journal, 2019)
Objective Alternative primary care structures such as group well-child care (GWCC) may enhance care for families, particularly those subject to structural vulnerabilities such as poverty or restrictive immigration policies. The purpose of this study was to characterize how group dynamics in GWCC impact the perceptions of low-income, immigrant, and/or Spanish-speaking parents of health services. Methods Using Spanish and English interview guides that were conceptually identical, we conducted semi-structured interviews with parents who elected to participate in GWCC at an urban academic center. We drew from directed content analysis, grounded theoretically in the Andersen model of health services utilization. Modeling a bilingual, multicultural analytic strategy, we preserved the narrative of participants in the source language through all stages of analysis. Results From March through August 2017, we interviewed 22 caregivers in their preferred language. Most (82%) were mothers and half spoke Spanish only. Three themes emerged: participants perceived that (1) GWCC facilitates their and their peers' discovery of inherent expertise, which moderates parents' use of health services, (2) GWCC encourages rearrangements of hierarchies of knowledge, professional roles and genders; and (3) in the context of structural vulnerabilities, relationships formed in GWCC facilitate collective efficacy. Conclusions for Practice By considering the self and peer as sources of health-related expertise, GWCC may extend current theoretical models of health services utilization. GWCC provides opportunities to impact health services utilization among families subject to structural vulnerabilities.
Keywords: *Child Health Services/sn [Statistics & Numerical Data]; *Child Welfare; *Parents/px [Psychology]; *Patient Acceptance of Health Care/sn [Statistics & Numerical Data]; Adolescent; Adult; Child Health Services; Child Welfare; Child, Preschool; Cultural diversity; Female; Humans; Interviews as Topic; Interviews as Topic/mt [Methods]; Male; Multilingualism; Parents; Patient Acceptance of Health Care; Patient Acceptance of Health Care/px [Psychology]; Primary health care; Qualitative Research; Qualitative research; Vulnerable populations; adolescent; adult; article; caregiver; case report; child; child care; child health care; child parent relation; child welfare; clinical article; content analysis; cultural diversity; dept.swk; drug efficacy; female; gender; group dynamics; health care utilization; human; human experiment; immigrant; interview; language; lowest income group; male; mother; multilingualism; narrative; patient attitude; peer-reviewed; perception; preschool child; primary health care; procedures; professional standard; psychology; qualitative analysis; qualitative research; semi structured interview; speech; vulnerable population

Management and Leadership in Social Work: A Competency Based Approach - Rofuth, Todd W.; Piepenbring, Julie M. (Springer Publishing Company, LLC, Springer Publishing Company, 2019)
The authors have had many years of leadership and management experience in a variety of settings and have discovered that there are few books that cover the majority of topics related to leadership and management specifically for social work education and practice. This book covers all the main areas of expertise required in a typical social work leadership and management experience. It incorporates all 21 competencies and 126 practice behaviors from the Network on Social Work Management (NSWM) and nine competencies and 29 practice behaviors espoused by the Council on Social Work Education (CSWE) and can serve as a textbook for social work programs at the graduate level. The book has many unique features. It provides a comprehensive list of leadership and management competencies from the NSWM and the CSWE along with a list of competencies and practice behaviors. The book presents leadership and management competencies and practice behaviors each chapter along with cases, examples, and activities of how to use them in practice situations. It discusses in detail the differences between management and leadership along with best management and leadership practices. The book provides examples of how to motive and successfully work with different age cohorts. It presents effective communication and marketing strategies. The book discusses in detail how to effectively work with groups and give examples of how to make meetings productive. It exhibits specific problem-solving and decision-making strategies along with examples. The book summarizes how to manage a range of organizational functions. It discusses the importance of collaborating with community groups and other stakeholders to succeed in making a difference. The book contains five parts that replicate the <abbrev>NSWM</abbrev>’s four domains of leadership: executive leadership in social work; resources management practices; strategic management and administrative skills for organizational growth and success; community collaboration; and supplemental materials.
Keywords: Leadership; Vocational qualifications; Social Work; dept.swk; faculty_collection; methods; Efficiency, Organizational; organization & administration; Leadership; Professional Competence; Personnel Management

Food in correctional facilities: A scoping review - Smoyer, Amy B. (Appetite, 2019)
In the last 20 years, there has been an exponential increase in research about food in prison. Given this growing interest, it is appropriate to take stock of the field by mapping and synthesizing existing knowledge in order to identify gaps in knowledge and make recommendations for future research. Specifically, the purpose of this scoping review is to understand the experiences of incarcerated people with food in order to inform interventions that will promote positive outcomes for justice-involved individuals and correctional facilities. This review identified 38 peer-reviewed research articles about food in correctional facilities. This sample included qualitative (n = 28) and quantitative (n = 10) research that explored the both the pragmatic and symbolic dimensions of food in these settings. Taken together, this body of research provides a rich description of prison food practices and the implications of these practices on medical, psychological, and sociological outcomes. Moving forward, collaboration between academics, incarcerated people, and correctional practitioners is encouraged in order to develop programs that use this research to improve individual and intuitional outcomes. In addition, while emerging research has begun to develop knowledge about prison food in developing countries, the literature focuses primarily on the US, Canada and Western Europe and there is a need to expand the geographic scope of this inquiry.
Keywords: *Food Services; *Prisons; Canada; Consumer Behavior; Europe; Food Services; Humans; Nutritive Value; Prisons; United States; Western Europe; adult; article; catering service; clinical article; consumer attitude; dept.swk; developing country; female; human; justice; male; nutritional value; peer-reviewed; physician; prison

Hygge: Food and the construction of safety among incarcerated women in Denmark - Smoyer, Amy B.; Minke, Linda Kjær (Appetite, 2019)
Knowledge about women's socio-emotional experience of incarceration is sparse. To address this gap in the research, open-ended interviews were conducted with 9 incarcerated women in Denmark. The inquiry focused on their experiences with prison food and eating, including questions about hygge-related practices. Hygge is a cherished part of Danish culture that encourages people to create cozy environments by sharing food and fellowship. While this warm and comforting practice may seem incongruent with prison, contemporary theory about carceral geography suggests a wide range of emotional spaces within prisons and identifies the central role of incarcerated people and external norms on constructing these spaces. The participants’ narratives describe and explain the role of hygge in Danish prisons. Participants report using food and other props to construct hygge in their cells, in common areas, and with visitors, in order to build safety and manage the harshness of prison life. While these experiences are fleeting, findings suggest that the ability of these women to engage in hygge practices has a deeply positive impact on their lived experience of incarceration. The findings expand understanding about the role of food in prison and inform the practices of correctional facilities.
Keywords: dept.swk; peer-reviewed

Social determinants of health: the how, who, and where screenings are occurring; a systematic review - O’Brien, Kyle H. (Social Work in Health Care, 2019)
Screening for social determinants of health allows health care teams to assess and address social factors that influence one’s health, mental health, and access to care. These social factors include poverty, health literacy, social support, exposure to trauma, food insecurity, and housing instability. The objective of this study was to examine what screening tools for social determinants of health are being used, in what contexts, and with what populations. Findings suggest that health literacy is the most commonly screened for, followed by trauma history, social support, food insecurity and housing across diverse contexts and populations. Results from this study can be used to inform providers of available screening tools and resources that can be readily utilized in practice. © 2019, © 2019 Taylor & Francis.
Keywords: Food Supply; Health Literacy; Health Services Accessibility; Health Status Indicators; Housing; Humans; Poverty; Social Determinants of Health; Social determinants of health; catering service; dept.hls; dept.rec; dept.swk; health care; health care delivery; health literacy; health status indicator; housing; human; integrated care; interprofessional practice; peer-reviewed; poverty; primary care; screening tools; social determinants of health

Voices should be heard: what personal stories of homelessness teach us about practice - Schneider, Dana A.; Cretella, Jill; Ranaudo, Sarah; Constantino, Daniel; Cota, Catherine F. (Families in society-The journal of contemporary social services, 2019)
The Voices Should Be Heard community-based participatory research project provided a platform for individuals experiencing homelessness to share their life stories and experiences. Participants offered their reflections on the oppression of homelessness and how the service delivery system could be improved. This article synthesizes these reflections and offers recommendations for practice aimed at reducing the oppression of homelessness and promoting social change. Using a strengths-based perspective, we offer points of entry for working with individuals experiencing homelessness.
Keywords: client-worker relationship; client–worker relationship; dept.swk; homelessness and housing; methods and analytics; modes of practice; peer-reviewed; professional issues; qualitative research; strengths-based practice; subjects of practice; working alliance

Hope, courage, and resilience in the lives of transgender women of color - Ruff, Nadine; Smoyer, Amy; Breny, Jean (The Qualitative Report, 2019)
There is a lack of qualitative and strengths-based knowledge about the lived experience of transgender women of color in the US. To address this research gap, a Photovoice project was undertaken with five transgender women living in a small urban area. Thematic analysis of the participants' discussion of their photographs identified three major themes: Hope, courage, and resilience. Analysis suggests a framework for understanding these women's lived experiences and the psychosocial tools that they use to negotiate their daily lives and persevere in the face of interpersonal and structural oppression. © 2019 Nova Southeastern University. All rights reserved.
Keywords: Courage; Hope; Photovoice; Resilience; Transgender Women; Women of Color; dept.pch; dept.swk; peer-reviewed; ⛔ No DOI found

Understanding the role of the brick-and-mortar classroom in course design and implementation of the “flipped” classroom: An exploratory case study - Counselman-Carpenter, Elisabeth; Redcay, Alex (Journal of Teaching and Learning with Technology, 2019)
Keywords: dept.swk; peer-reviewed

The Arc of Justice: Examining Policies and Laws to Advance the Human Rights of Transgender and Gender Expansive Children - Redcay, Alex; Counselman-Carpenter, Elisabeth; McMahon, Sheila; Luquet, Wade; Rice, Karen; Lance, Roseanna (Journal of Human Rights and Social Work, 2019)
The role of the social worker in the achievement of human rights is to assist individuals in their struggle for dignity and their attainment of their full potential. Ethical social work ensures just laws and practices that allow all persons to live without discrimination. The purpose of this paper is to present the practice and policy implications of the last five years of court cases regarding transgender and gender expansive (TGE) children and school systems in the USA. This paper outlines the legal justifications for revisions to the current procedures and policies of interacting with TGE children, including use of restrooms consistent with gender identity (RCGI). These recommended guidelines are designed to prevent ongoing human rights violations and create pathways for TGE children to live their lives congruently with their gender identity. Basic human rights for the TGE individual include policy improvements involving restrooms, locker rooms, showers, overnight accommodation, affirmed name, and identification for the child welfare, mental health, educational, medical, juvenile justice, and law enforcement systems. © 2019, Springer Nature Switzerland AG.
Keywords: Ethics; Gender expansive children and youth; Policy; Transgender; dept.swk; peer-reviewed

Provider Attitudes, Organizational Readiness for Change, and Uptake of Research Supported Treatment - Bornheimer, Lindsay A.; Acri, Mary; Parchment, Tyrone; McKay, Mary M. (Research on Social Work Practice, 2019)
Purpose:As implementation and evaluation of research supported treatment (RST) expands across diverse mental health settings, it is essential to understand the facilitators and inhibitors of uptake. The current study examined the relationships between organizational readiness for change, attitudes toward RST, and use of RST among a sample primarily of social workers.Methods:Participants included 158 providers from public child mental health outpatient clinics in the New York metropolitan area. Data were analyzed using structural equation modeling.Results:Use of RST was greater among providers who were younger and had fewer years of professional experience. Both organizational need for change and climate directly and indirectly related to use of RST through attitudes toward RST (partial mediator).Discussion:The organizational context is an important factor that relates to attitudes toward and use of RST in practice. Future research is needed to continue examining factors of RST uptake and sustainability.
Keywords: dept.swk; organizational readiness for change; provider attitudes; research supported treatment; treatment uptake

Teaching note—MSW student perceptions of learning advanced clinical practice skills through the flipped classroom - Counselman-Carpenter, Elisabeth A. (Journal of Social Work Education, 2019)
The flipped classroom, with its focus on student-centered learning and active student engagement, is a growing trend in social work education. This article presents an innovative way of delivering practice content through the flipped classroom model, which can be adapted for any level of social work education. It walks readers through the steps of developing the course and the successes and challenges of the flip, particularly with an incorporated skills lab component. Additionally, this article shares student reflections on the development and execution of the course, with specific feedback on the experiential learning environment, discussions surrounding instructor workload and preparation, and implications for future iterations of the course from students who had very little prior technologically centered learning experiences.
Keywords: dept.swk; peer-reviewed

Older adults’ lived experience of incarceration - Smoyer, Amy B.; Madera, Johanna Elumn; Blankenship, Kim M. (Journal of Offender Rehabilitation, 2019)
This qualitative analysis explores older adults’ lived experiences of incarceration. As part of a larger mixed-methods longitudinal study, 23 older adults were interviewed about their prison and reentry experiences. Findings describe experiences of loss, lack of medical attention, abuse by staff and other inmates, and the uncertainties and danger of prison life. After release, participants reported experiencing anxiety and stress related to their prison experiences. While participants reported that the ability to manage prison life deteriorated with age, some benefits of their senior status were also described. Maturity may allow older prisoners to remove themselves from volatile situations. Participants described experiences of rest and recovery, reflecting coping mechanism and resilience that could improve psychosocial outcomes during and after prison. This descriptive analysis centers the voices of older prisoners and informs interventions to support this vulnerable community.
Keywords: Prison; dept.swk; incarceration; older people; peer-reviewed; qualitative; reentry

Prepared to care: an exploration of continuing education trends of nurses caring for injured children - Roney, Linda Nancy; Acri, Mary C. (Journal of Trauma Nursing, 2019)
The significance of nursing competence in the care of pediatric trauma patients has been well documented. Continuing education for trauma nurses is a critical component of maintaining competence in pediatric trauma care; yet, there is significant variability in the programs and resources used to support this goal. The purpose of this current study was to describe the educational activities that practicing registered nurses engage in to inform their care of injured children. A quantitative, descriptive nonexperimental research design was utilized to describe the educational programs that members of the Society of Trauma Nurses (STN) must complete to work in verified and designated trauma centers. Participants completed a survey instrument that included demographic questions, pediatric trauma educational programs required/offered by their employer, and feedback about pediatric trauma nursing education. A total of 266 STN members completed the electronic survey, reflecting a 9% response rate. Most of the participants reported that the verifying body required trauma nursing education hours (n = 187, 70.3%). The number of required courses ranged from 1 to 6, with 33 (12.4%) reporting this 3-course combination-emergency nursing pediatric course (ENPC), pediatric advanced life support (PALS), and trauma nursing core course (TNCC). The second most common combination of courses (n = 30; 11.3%) was required to take both PALS and TNCC. No significant relationship was found between verifying agency type and continuing education program required (p¿ .05). Trauma nursing core course was the most popular course (n = 208; 79%), followed by PALS (n = 194; 73%) and ENPC (n = 103; 38%). Participants also shared barriers to continuing education activities. It has been 10 years since pediatric trauma nursing course utilization was first explored in the literature. There continue to be significant opportunities to support nurses in continuing education activities related to the care of injured children. While barriers to accessing these types of activities sometimes exist, it is the responsibility of the pediatric trauma community to explore these challenges even further and collaborate with others interested in improving the care of injured children.
Keywords: Child; Child Health Services; Clinical Competence; Education, Nursing, Continuing; Emergency Nursing; Female; Humans; Male; Nursing Staff, Hospital; Pediatric Nursing; Pediatric trauma; Pediatric trauma nursing; Surveys and Questionnaires; Trauma education; Trauma verification; child; child health care; clinical competence; dept.swk; education; emergency nursing; female; human; male; nursing education; nursing staff; pediatric nursing; peer-reviewed; questionnaire

Crowdsourced social work educator technology standards - Counselman-Carpenter, Elisabeth (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Applying accessibility practices across a curriculum - Marquart, M; Counselman-Carpenter, E (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Case study – teaching online with students who are deaf - Marquart, M; Counselman-Carpenter, Elisabeth (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Louis Lowy - Sozialarbeit unter extremen Bedingungen: Lehren aus dem Holocaust - Gardella, Lorrie Greenhouse (Lambertus-Verlag, 2019)
Keywords: dept.swk

Repair the world: Group work in the Deggendorf Displaced Persons Center, 1945-1946 - Gardella, Lorrie Greenhouse (Groupwork, 2019)
This paper explores the formation of a transitory community in the UNRRA Displaced Persons Center in Deggendorf, Germany, where Jewish Holocaust survivors used social group work to preserve their past, to restore humane values, and to prepare for new lives.  Social activism through task groups and activity groups affirmed individual and community self-determination while promoting recovery from trauma.  The experience of the She’erith Hapleitah or “surviving remnant,” as they called themselves, though historically specific, has implications for group work with migrants today.
Keywords: Citizenship; Groupwork; Holocaust survivors; Hope; Migrants; Recovery; Refugees; dept.swk; peer-reviewed

The impact of fluid attraction and fluid identity on mental health - Redcay, Alex; Counselman-Carpenter, Elisabeth; Proctor, Curtis (Journal of Gay & Lesbian Mental Health, 2019)
Using data from the National Longitudinal Study of Adolescent Health, this study examined the impact of sexuality factors and satisfaction with partner on stress, anxiety, and depressive symptoms. Multiple regression was used to evaluate the impact of predictors such as sexuality factors and relationship satisfaction on the dependent variables: stress, anxiety, and depression. Three main results were discovered. First, sexual minority females who have lower levels of education and are dissatisfied with their relationship experience significantly higher stress, while sexual minority males do not differ from heterosexual males in terms of relationship satisfaction or stress. Second, sexual minority females who have lower levels of education and who are dissatisfied with their relationship experience significantly higher anxiety, while sexual minority males do not differ from heterosexual males in terms of relationship satisfaction or anxiety. Finally, female sexual minorities who have lower levels of education reported fluid attraction, fluid identity, dissatisfaction with their relationship, and have significantly higher depression when compared to male sexual minorities or heterosexuals. Further research should examine gender and fluidity in greater detail. © 2018, © 2018 Taylor & Francis Group, LLC.
Keywords: Anxiety; depression; dept.swk; fluid attraction; fluid identity; peer-reviewed; satisfaction with partner; sexual orientation; stress

Examining the impact of psychological factors on hospital length of stay for burn survivors: A systematic review - O’Brien, Kyle H; Lushin, Victor (Journal of Burn Care & Research, 2019)
Recovery of burn patients may be impeded by mental health problems. By gaining a better understanding of the impact that psychological factors may have on hospital length of stay, providers may be better informed to address the complex needs of burn survivors through effective and efficient practices. This systematic review summarizes existing data on the adverse psychological factors for the length of burn patients' hospitalization, and assesses the methodological quality of the extant literature on mental health conditions of burn survivors. A literature search was conducted in four electronic databases: PubMed, PsychINFO, Science Direct, and the Cumulative Index to Nursing and Allied Health Literature. Results yielded reports published between 1980 and 2016. Methodological quality was assessed by using an 11-item methodological quality score system. Seventy-four studies were identified by search; 19 articles were eligible for analysis. Findings demonstrate paucity of evidence in the area. Reports indicate longer hospital stay among burn patients with mental health problems. Substance use was the most consistent mental-health predictor of longer hospital stay. Heterogeneity in data on mental health conditions rendered impossible estimation of effect sizes of individual psychological factors on length of hospitalization. Many studies over-relied on retrospective designs, and crude indicators of psychological factors. Findings indicate that mental health problems do have an impact on the trajectory of burn recovery by increasing the length of hospital stay for burn survivors. Inpatient mental health services for burn patients are critically needed. Prospective designs, and more sensitive psychological indicators are needed for future studies.
Keywords: Article; Burns; Hospitalization; Humans; Length of Stay; Survivors; burn; burn patient; burn survivor; dept.hls; dept.rec; dept.swk; distress syndrome; hospitalization; human; length of stay; mental disease; mental health; peer-reviewed; psychological aspect; psychology; substance use; survivor; systematic review

Realizing the potential for leadership in social work - Keenan, Elizabeth King; Sandoval, Silvia; Limone, Christine (Journal of Social Work, 2019)
Ongoing racism, structural inequity, dehumanizing institutional bureaucracies, unresponsive service delivery systems, and gaps in services for emerging needs are just some of the pervasive challenges in need of social work leadership. The multidisciplinary nature of social work practice also requires value-based leadership processes on multiple ecological levels to address the challenges inherent within social delivery systems. Social work encourages all social workers to lead these change efforts, but research on front-line social work leadership is lacking. Constructionist conceptualizations of leadership as social influence processes provide a unit of analysis to examine front-line leadership. A secondary analysis of qualitative data examining social work practice that promotes well-being and social justice revealed leadership processes in multiple social work practice settings. Findings Front-line social workers demonstrate three overarching leadership processes in their practice: challenging injustice and changing mindsets, conduit for change, and organizing resources and relationships. Applications Conceptualizing leadership as social influence processes identifies and acknowledges the leadership of front-line social workers, expanding the profession's capacity to collectively articulate and initiate change with a range of social problems and systemic challenges in organizations and communities.
Keywords: Social work; article; dept.swk; health care delivery; human; leadership; occupation; peer-reviewed; qualitative research; racism; secondary analysis; social constructionism; social justice; social work; social work practice; wellbeing

The Positive Assessment: A Model for Integrating Well-Being and Strengths-Based Approaches into the Child and Adolescent Psychiatry Clinical Evaluation. - Schlechter, Alan Daniel; O'Brien, Kyle H; Stewart, Colin (Child and adolescent psychiatric clinics of North America, 2019)
In traditional medical practice, the diagnostic interview is focused on symptom collection, diagnosis, and treatment. The psychiatric interview is based on the medical model, but mental health clinicians lack the tests found in general medicine. Rapport is the most essential tool for the psychiatrist to uncover symptoms and develop a diagnosis and treatment plan. This article brings a scientific lens to the psychiatric interview. Under this microscope the value of eliciting the patient's well-being at the outset of the interview becomes clear. Using positive psychology, an evidenced-based rationale for the positive assessment is outlined and methodology and practice of the assessment reviewed. Copyright © 2018 Elsevier Inc. All rights reserved.
Keywords: *Adolescent Psychiatry; *Child Psychiatry; *Child Welfare; *Mental Disorders/di [Diagnosis]; Adolescent; Adolescent Psychiatry; Assessment; Caregivers; Child; Child Psychiatry; Child Welfare; Common factors theory; Diagnostic interview; Humans; Mental Disorders; Neurosciences; Positive emotions; Positive psychology; Psychiatry; Psychiatry interview; Rapport; Review; Well-being; achievement; adolescent; caregiver; child; child psychiatry; child welfare; clinical evaluation; dept.hls; dept.swk; doctor patient relationship; emotion; human; mental capacity; mental disease; mental health; motivational interviewing; neuroscience; patient assessment; peer-reviewed; priority journal; psychiatry; psychological interview; psychological well-being; reward; social life

Self care - Counselman-Carpenter, Elisabeth (Working with grief & traumatic loss: Theory, practice, personal reflection and self-care for clinicians, 2019)
Keywords: dept.swk

Remembering Jim Garland: Loneliness in the group - Gardella, Lorrie Greenhouse (Group work: Creating space for all voices, 2019)
Keywords: dept.swk